1994
DOI: 10.1002/cyto.990170212
|View full text |Cite
|
Sign up to set email alerts
|

TO‐PRO‐3 iodide: A novel HeNe laser‐excitable DNA stain as an alternative for propidium iodide in multiparameter flow cytometry

Abstract: A new red emitting fluorophore, TO-PRO-3 iodide (TP3), which is best excited by an HeNe laser (633 nm), has been compared with propidium iodide (PI) for measuring relative DNA content. TP3, which has a peak absorbance at 642 nm and emission at 661 nm, has been tested on peripheral blood lymphocytes (PBL) and keratinocytes in a two-laser system. As an example, we present a three-color flow cytometric application utilizing TP3 in combination with fluorescein-isothiocyanate (FITC) and phycoerythrin (PE) conjugate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
61
0
1

Year Published

1997
1997
2008
2008

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(63 citation statements)
references
References 16 publications
1
61
0
1
Order By: Relevance
“…The level of TO-PRO-3 incorporation into cellular DNA is indicative of significant membrane injury and has been widely used to distinguish dead from living cells (Van Hooijdonk et al, 1994). Our previous results showed that pyramidal neuron survival was variable after a 15 min.…”
Section: To-pro-3 Iodide Staining and Quantification Of Neuronal Viabmentioning
confidence: 98%
See 1 more Smart Citation
“…The level of TO-PRO-3 incorporation into cellular DNA is indicative of significant membrane injury and has been widely used to distinguish dead from living cells (Van Hooijdonk et al, 1994). Our previous results showed that pyramidal neuron survival was variable after a 15 min.…”
Section: To-pro-3 Iodide Staining and Quantification Of Neuronal Viabmentioning
confidence: 98%
“…It labels DNA in cells only with compromised cell membranes (Van Hooijdonk et al, 1994). Exposure to OGD for 20 min.…”
Section: Ogd Induced Acute Neuronal Death Was Largely Attenuated By Rvtmentioning
confidence: 99%
“…After the last centrifugation and supernatant discard, cells were transferred to microtubes in a final volume of 250 L of PBS or To-Pro-3 iodide (Molecular Probes, Eugene, OR). The latter was used for viability gating as needed (10,11). The microtubes were inserted into corresponding 12 ϫ 75 mm tubes in the loader rack of a FACScalibur flow cytometer (Becton, Dickinson [BD], San Jose, CA) for data acquisition.…”
Section: Cell Surface Stainingmentioning
confidence: 99%
“…TO-PRO-3 seems to be best suited for multicolor analysis, and already has been utilized for the multi-parameter flow cytometric analysis [6,7,27]. But, it has one shortcoming: fluorescence instability under laser illumination [18,24].…”
Section: Prevention Of the Photobleaching Of Dna-specific Fluorocmentioning
confidence: 99%